The Study of Children's Literature: Internalization of Cultural Values and Exploration of Social Issues - Michelia Rahmina; Ahadi Sulissusiawan; Agus Wartiningsih (CV. Publikasi Indonesia, 2024)
This research aims to present an in-depth study of the role of children's literature as a medium for internalizing cultural values and exploring social issues. The aspects discussed in this research are obtained from library research on related research, then presented with descriptive analytical methods. Based on the results of the study, it can be concluded that children's literature with the mission of dulce et utile (entertaining and useful) plays an important role in the practice of character education, introducing cultural values, and sharpening sensitivity to social issues. The interaction between children and children's literature usually requires the role of adults as facilitators of literary works, especially in the pre-literacy phase which does not allow children to read literacy symbols independently. The practical implications that need to be considered by parents and teachers relate to four major classifications, namely considering the relevance of the work to the child's condition; adjusting the formulation of language content to the language skills of children/learners; using illustrations/intonation in the delivery of literary works (especially for children/learners who are not yet able to read independently); and providing direct assistance when children/learners interact with literary works. The mission of literature as an evocator of human consciousness (especially children, in this context) requires collaboration from various parties. Parents, educators, children's literature writers, and even the government as policy makers need to play an active role and realize the urgency of implementing children's literature in their learning.